Islamic Corporate Social Reporting (ICSR): Comparing the Desirable, the Desired and the Actual - Muhamad, Rusnah; Abdul Rahman, Zulfa; Lin, Tan Ai (Asian Journal of Accounting Perspectives, 2014)
Various authors have suggested that culture is a powerful environmental factor, and, therefore, it has the potential to influence the development of the accounting system and practices of a country. In addition, it is claimed that culture also affects the perception and use of the accounting information by individuals. Religion is considered to be a significant cultural factor, and, thus, may have an impact on accounting practices. More specifically, Islam, a religion that is considered to be a way of life (ad-din) that transcends geographical, racial and linguistic differences, has the potential to influence the structure, underlying concepts and the mechanisms of accounting in the Islamic world. In Malaysia, there has been some evidence of corporate social reporting (CSR) among organisations in the absence of any regulatory or legal requirements. This study aims to compare the desirable, the desired and the actual in reporting corporate social responsibility from an Islamic perspective. The empirical study is carried out to identify whether there is any gap in CSR between the desirable (as prescribed by shariah), the desired (as perceived by Malay Muslim accountants) and the actual practices (as observed from the current reporting practices of selected Islamic Business Organizations (IBOs)).